2008
DOI: 10.1074/jbc.m708466200
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 Stimulates Proliferation and Enhances Tumorigenesis of Human Breast Epithelial Cells

Abstract: The scaffold protein IQGAP1 integrates signaling pathways and participates in diverse cellular activities. IQGAP1 is overexpressed in a number of human solid neoplasms, but its functional role in tumorigenesis has not been previously evaluated. Here we report that IQGAP1 contributes to neoplastic transformation of human breast epithelial cells. The amount of IQGAP1 in breast carcinoma is greater than that in normal tissue, with highly metastatic breast epithelial cells expressing the highest levels. Overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 66 publications
11
143
0
2
Order By: Relevance
“…Although this does not prove that IQGAP1 plays a role in tumor suppression, the result is consistent with the knockout mouse studies that suggest that IQGAP1 is a negative regulator for cancer development. We also examined IQGAP1 expression in breast cancer tissues and their adjacent pathologically normal tissues and found that indeed, IQGAP1 was up-regulated in breast cancer tissue, similar to findings in other previously reported studies (33). moreover, IQGAP1 knockdown experiments showed that reduction of IQGAP1 resulted in increased cell growth in non-cancer breast epithelial cells but resulted in decreased cell growth in breast cancer cells, supporting that IQGAP1 plays an opposite role in normal development and cancer.…”
Section: Discussionsupporting
confidence: 67%
“…Although this does not prove that IQGAP1 plays a role in tumor suppression, the result is consistent with the knockout mouse studies that suggest that IQGAP1 is a negative regulator for cancer development. We also examined IQGAP1 expression in breast cancer tissues and their adjacent pathologically normal tissues and found that indeed, IQGAP1 was up-regulated in breast cancer tissue, similar to findings in other previously reported studies (33). moreover, IQGAP1 knockdown experiments showed that reduction of IQGAP1 resulted in increased cell growth in non-cancer breast epithelial cells but resulted in decreased cell growth in breast cancer cells, supporting that IQGAP1 plays an opposite role in normal development and cancer.…”
Section: Discussionsupporting
confidence: 67%
“…Interest in such finessed approaches to chemotherapeutic target exploitation is clearly increasing, as evinced by the growing body of work with IQ motif-containing GTPase activating protein 1 (IQGAP1) a scaffold within the MAPK pathway that is responsible for assembling the kinases within this pathway to effect signal transmission [66,67]. IQGAP1 has been linked to the progression of cancer and drives tumourigenesis in both mouse models and human tissue [66,68]. Up-regulation of the ERK1/2 MAPK cascade is seen in 30% of cancers and IQGAP1 binds to ERK1/2 through a highly conserved 32 amino acid 'WW domain' to facilitate activation of ERK in response to certain stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP1 has been reported to interact with βArr2, a scaffold protein that binds to activated GPCRs and regulates signaling and receptor endocytosis (20). IQGAP1 promotes proliferation and migration, and overexpression has been associated with poor prog-nosis in advanced colorectal cancer (21)(22)(23). Interestingly, IQGAP1 can coordinate cell growth and division in a phosphorylation-dependent manner (24).…”
Section: Gpr161 Induces Migration and Invasion Of Mammary Epithelial mentioning
confidence: 99%